Bibliometric Analysis: The Application of Augmented Reality in the Field of Education in the World - Triani, Deswinta; Sudarshana, Midigama Liyanage (CV Media Inti Teknologi, 2025)
The research conducted is a bibliometric analysis related to the application of augmented reality in the field of education in the world. It aims to investigate its application in world education, how it affects students' learning skills, and provides insights for future educational practices. Utilizing the Publish or Perish tool, the research methodology employed a keyword search for